2021
DOI: 10.1055/s-0041-1731763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Suprafascial Thin ALT Flap in Foot and Ankle Reconstruction

Abstract: Background Distal lower extremity reconstruction can be challenging in terms of flap design. Bulky flaps result in limited mobility accompanied with the need of customized footwear. Raising the ALT-flap in a superficial fascial plane (thin ALT-flap) can be beneficial. This study evaluates thin ALT-flaps for lower distal extremity reconstruction. Methods In a retrospective study, patients that underwent microvascular extremity reconstruction at the level of the ankle and dorsal foot at the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…The safety of secondary flap elevation is also of interest for esthetic revision procedures, which Nelson et al 14 estimated to occur in 21% of lower extremity salvage cases. While Thiele et al 30 found that fascial flaps had the highest revision success rate in a series of foot and ankle reconstruction cases, our cohort of tibia flaps had similar rates of secondary elevation success between muscle and fasciocutaneous flaps. This discrepancy may be due to high volume of distal extremity reconstruction at our center and/or better soft tissue envelope of the tibia compared with the foot and ankle.…”
Section: Discussionsupporting
confidence: 47%
“…The safety of secondary flap elevation is also of interest for esthetic revision procedures, which Nelson et al 14 estimated to occur in 21% of lower extremity salvage cases. While Thiele et al 30 found that fascial flaps had the highest revision success rate in a series of foot and ankle reconstruction cases, our cohort of tibia flaps had similar rates of secondary elevation success between muscle and fasciocutaneous flaps. This discrepancy may be due to high volume of distal extremity reconstruction at our center and/or better soft tissue envelope of the tibia compared with the foot and ankle.…”
Section: Discussionsupporting
confidence: 47%
“…This may be the current ideal modality to map the distinctive planes of potential elevation as well as the vascular pathway in the same position as if in surgery. 25,[31][32][33][34] There was a 100% correlation between the preoperative perforator mapping using duplex color ultrasonography and intraoperative findings. 22 In addition to the vascular pathway and vessel diameter, peak velocity and flow volume can be calculated to evaluate the physiologic aspect of the proposed flap.…”
Section: Videomentioning
confidence: 87%
“…14 However, in this study most of these free flaps were applied for remote traumatic injury. 14 The incidence of unreliably small or absent perforators among ALT flap was reported to range from 2.7 to 4.8%. 10,15 In order to save the time during flap harvest, computed tomography angiography (CTA) and color duplex ultrasound (CDU) can be used for preoperative planning.…”
Section: Discussionmentioning
confidence: 98%
“…This theoretically leads to a thinner flap and precludes the need for secondary debulking procedures, which can decrease this cost. 14 However, in this study most of these free flaps were applied for remote traumatic injury. 14…”
Section: Discussionmentioning
confidence: 98%